2011
DOI: 10.1002/chem.201101322
|View full text |Cite
|
Sign up to set email alerts
|

Left or Right? The Direction of Compression‐Generated Vortex‐Like Flow Selects the Macroscopic Chirality of Interfacial Molecular Assemblies

Abstract: A new method is described through which the macroscopic chirality of interfacial molecular assemblies of an achiral porphyrin can be mechanically controlled using an original yet efficient Langmuir-Blodgett (LB) technique. By using the unilateral compression geometry, we find that the assemblies deposited from the mirror regions of the LB trough display mirror macroscopic chirality. It is indicated that vortex-like flows could be generated during compression, and that it is the direction of this compression-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 57 publications
(14 reference statements)
2
54
0
Order By: Relevance
“…80%) samples display negative CD signals. These statistical results show a similar tendency to those of the samples constructed by using a compression speed of 0.2 mm per second, 25 preliminarily suggesting that the compression direction and/or the deposition region might be the main factor that determines the macroscopic chirality of the interfacial assemblies, while the compression speed might contribute less to this issue.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…80%) samples display negative CD signals. These statistical results show a similar tendency to those of the samples constructed by using a compression speed of 0.2 mm per second, 25 preliminarily suggesting that the compression direction and/or the deposition region might be the main factor that determines the macroscopic chirality of the interfacial assemblies, while the compression speed might contribute less to this issue.…”
Section: Resultssupporting
confidence: 84%
“…25 As shown in Fig. 1A (top panel), for typical samples assembled by compression from the left-hand side, the assemblies formed at the front side of the Langmuir trough exhibit a negative CD signal around 438 nm, while those formed at the back side of the trough display a mirror-imaged CD curve.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…More striking is the report that the combination of soft aggregation and stirring may lead not only to chiral induction 22,23 but, more importantly, also to sign selection, in both three 24,25 and two dimensions 26,27 . Discussions on the true nature of such an enantioselection in three-dimensional aggregates have raised some controversy [28][29][30][31][32][33] .…”
mentioning
confidence: 99%
“…[26] Consequently, patterned nanoarrays, nanostripes, nanofibers, nanoparticles, nanotubes, and even chiral assemblies could be fabricated. [24,[27][28][29][30] For example, Chen et al reported that by taking the advantage of their thinner and flexible gold nanowires (AuNWs) building blocks, giant superlattice nanomembranes could be fabricated via LB techniques. [31,32] It was found that high transparency, conductivity, and stretchability could be achieved simultaneously in such single-layer AuNWs superlattice nanomembrane, which make them facile to be integrated into lightweight, foldable optoelectronic devices with low consumption of materials and energy.…”
Section: Controllable Nanoassembly Of π-Conjugated Systemsmentioning
confidence: 99%